Contextual factors influencing schistosomiasis treatment and identification of delivery platforms for arpraziquantel in hard-to-reach areas and populations in Homa Bay County, Kenya. - Phyllis Munyiva Isaiah; Doris Osei Afriyie; Mary Maghanga; Donna Obare Ogeto; Mary Amuyunzu Nyamongo; Peter Steinmann (PLOS Global Public Health)
A new formulation of praziquantel, arpraziquantel (arPZQ), has been developed for preschool-aged children (PSAC) to fill the treatment gap for this age group in schistosomiasis control and elimination programs. There is now a priority to ensure that the drug reaches all at-risk PSAC in endemic areas, including hard-to-reach areas and populations. This study aimed to determine schistosomiasis treatment-related contextual factors among fishermen and island populations in Homa Bay County, Kenya, and to identify a suitable platform to deliver arPZQ. We conducted a generic qualitative study using two case study interviews with parents/caregivers living with disability caring for children ≤5 years,18 focus group discussions (FGDs) with parents/caregivers of children ≤5 years (each with 8-10 participants), 14 key informant interviews (KIIs) with various government agencies, and unstructured observations. The data were analyzed using thematic analysis. The case study interviews and FGDs revealed awareness of schistosomiasis among community members but limited knowledge of transmission risk factors. Lake water and open defecation were the main predisposing factors to infection. We observed poor health-seeking behavior in the community due to inaccessibility of quality healthcare services, resulting from health system level, population level, and geographic barriers. Despite these barriers, community members reported positive experiences with previous PZQ mass drug administration (MDAs) and other innovative healthcare programs, and expressed willingness to participate in future MDAs, including with arPZQ. Based on the reported barriers, the door-to-door distribution approach by community health promoters was proposed by parents and key informants as the most feasible platform for community sensitization, mobilization, and arPZQ delivery. To achieve high arPZQ treatment coverage for all at-risk PSAC, and promote ownership and sustainability of the program, the door-to-door approach is the most promising platform to deliver treatment and public health promotion in marginalized hard-to-reach island populations of Lake Victoria, Kenya.